Phosphorus recovery by mesoporous structure material from wastewater - Lee, S. H.; Lee, B. C.; Lee, K. W.; Lee, S. H.; Choi, Y. S.; Park, K. Y.; Iwamoto, M. (IWA PUBLISHING, 2007)
This study was designed to investigate the fundamental aspects of a possible removal of phosphorous from wastewater by using the mesoporous structure materials for wastewater reuse. The zirconium sulphate with mesoporous structure as a new type of ion exchangers was synthesised by hydrothermal reaction. From the results of X-ray diffraction and transmission electron microscope, it was discovered that the synthesised material had hexagonal mesoporous structure with a pore size of approximately 40-50 angstrom. Experimental results showed that the zirconium sulphate with mesoporous structure had very high sorption capacity for the phosphorus. The novel ion exchange occurred between PO43- and SO42-, OH-. The amount of phosphate ions exchanged into the solid was as great as 3.4 mmol/g-ZS. Furthermore, it is possible to obtain a higher removal efficiency than other ion exchange media and adsorbents.
Keywords: PHOSPHATE